2017
DOI: 10.1111/ped.13300
|View full text |Cite
|
Sign up to set email alerts
|

Febrile status epilepticus due to respiratory syncytial virus infection

Abstract: RSV infection in the absence of bronchiolitis can initially present as febrile status epilepticus and subsequently develop into acute encephalopathy with profound neurological sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The olfactory receptor (OR13C5) gene is also involved in RSV pathogenicity, since the olfactory nerve connects the nasal cavity with the central nervous system and thus could be used as a shortcut by RSV (136). This could explain neurological symptoms produced by RSV such as encephalitis, apnea, or seizures, that occur in at least 2% of RSV-infected people (137, 138), and likely cause serious and permanent neurological sequelae (139). SNPs in human leukocyte antigen (HLA) HLA-DQA1 and in HLA-DPB1 genes have been associated with the development of bronchiolitis and several types of asthma (140142).…”
Section: Host Components Contributing To Rsv Pathogenesismentioning
confidence: 99%
“…The olfactory receptor (OR13C5) gene is also involved in RSV pathogenicity, since the olfactory nerve connects the nasal cavity with the central nervous system and thus could be used as a shortcut by RSV (136). This could explain neurological symptoms produced by RSV such as encephalitis, apnea, or seizures, that occur in at least 2% of RSV-infected people (137, 138), and likely cause serious and permanent neurological sequelae (139). SNPs in human leukocyte antigen (HLA) HLA-DQA1 and in HLA-DPB1 genes have been associated with the development of bronchiolitis and several types of asthma (140142).…”
Section: Host Components Contributing To Rsv Pathogenesismentioning
confidence: 99%
“…The seven studies that were not suitable for prevalence‐of‐intubation pooling had cohorts that consisted entirely of those that were intubated, making a calculation of prevalence impossible . A comprehensive listing of the 46 articles with a description of study characteristics, prevalence‐bias assessment, and intubation prevalence are shown in Table S1 …”
Section: Resultsmentioning
confidence: 99%
“…They authors reported the cases of 9 patients, of which 4 (44%) were complicated by cardiac arrest, and 2 of the patients died [5]. Uda and Kitazawa [8] reported that the RSV-positive status epilepticus group required more ventilator care and antiepileptic drug treatment than did the RSV-negative status epilepticus group, and nearly one-third of them developed encephalopathy and profound neurological sequelae. In the present study, encephalopathy with seizure was rare and observed in only one patient.…”
Section: Discussionmentioning
confidence: 99%
“…As in other common viral infections, RSV may be associated with neurological manifestations, including seizures, encephalopathy, extraocular movement disorder, and central apnea [3-8]. Although the pathogenesis of the neurologic complications are not fully understood, the possible contributions of immune-related cytokine responses, less well-proven direct invasion of virus particles, and brain stem-related mechanisms for respiratory control have been recognized [3,5,9-11].…”
Section: Introductionmentioning
confidence: 99%